Motivational factors affecting entrepreneurial decision: A comparison between Malaysian women entrepreneurs and women non entrepreneurs - Raman, Kavitha; Anantharaman, Reddiyoor Narayanaswamy (IBIMA Publishing, 2008)
This paper examines the motivational factors that could possibly lead women to become entrepreneurs. A comparison of these motivational factors is clone between women entrepreneurs and women non-entrepreneurs. The study is based on 225 women entrepreneurs, engaging in the manufacturing, trading and services sectors in Small and Medium Industries in Malaysia. Non-entrepreneurs consist of women working in various administrative departments. Motivation factors are classified into economic core, work core, social core, individual and entrepreneurial core. Descriptive analysis revealed some very important motivation factors. A discussion on the demographical profile of women entrepreneurs is also provided.